Transport and matching of the injecting beam - Belikov, А.G.; Bondarenko, L.А.; Vdovin, S.А.; Gussev, Ye.V.; Manuilenko, O.V.; Shulika, N.G. (Вопросы атомной науки и техники, 2018)
The properties of multi-element axially symmetric electrostatic lenses as a possible matching device of linear accelerator injector are considered. The electrostatic lenses are more effective at small (up to 150 keV) injection energy which used for small sized linear accelerators of ions. The criteria for choosing the most suitable lens parameters
are discussed. The results of five-electrode lens study are presented. The investigation was carried out by a numerical method. Preliminary modeling was carried out applying original programs developed at NSC KIPT in which
numerical code based on the integral equations method for calculating the distribution of the field strength between
the electrodes of a lens was used. For a detailed numerical study of the five-electrode electrostatic lens, was used a
package of three-dimensional computer simulation of charged particle optics – IBSimu. Розглянуті властивості багатоелектродних оксіально-симетричних електростатичних лінз в якості пристрою інжектора лінійного прискорювача іонів, що транспортує та узгоджує. Такі лінзи найбільш ефективні
в області малих (до 150 кеВ) енергій інжекції, які використовуються у малогабаритних прискорювачах іонів.
Обговорюються критерії вибору параметрів лінз. Представлені результати дослідження п’ятиелементної
лінзи. Дослідження проводилося чисельним методом. Попереднє моделювання виконано з використанням
оригінальних програм, розроблених у ННЦ ХФТІ, в яких для розрахунку розподілу напруженості поля між
електродами лінзи використаний чисельний код на основі методу інтегральних рівнянь. Детальне дослідження п'ятиелектродної електростатичної лінзи було виконано з використанням пакету тривимірного комп'ютерного моделювання оптики заряджених частинок – IBSimu. Рассмотрены свойства многоэлементных аксиально-симметричных электростатических линз как возможного согласующего устройства инжектора линейного ускорителя ионов. Такие линзы наиболее эффективны в области малых (до 150 кэВ) энергий инжекции, используемых в малогабаритных ускорителях
ионов. Обсуждаются критерии выбора наиболее подходящих параметров линз. Представлены результаты
исследования пятиэлементной линзы. Исследование проводилось численным методом. Предварительное
моделирование выполнено с использованием оригинальных программ, разработанных в ННЦ ХФТИ, в которых для расчёта распределения напряжённости поля между электродами линзы использован численный
код на основе метода интегральных уравнений. Детальное исследование пятиэлектродной электростатической линзы было выполнено с использованием возможностей пакета трехмерного компьютерного моделирования оптики заряженных частиц – IBSimu.